2021
DOI: 10.3390/ijerph18137032
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Student-Athletes’ Identity, Mental Health, and Social Support in Japanese Student-Athletes during the COVID-19 Pandemic

Abstract: The purpose of the two studies was to investigate the relationships among student athletes’ identity and mental health during the COVID-19 pandemic. In addition, this study aimed to clarify the relationship between perceived social support from teammates and mental health in student-athletes. Two studies were conducted to investigate and clarify the mental health states of student-athletes in Japan during the COVID-19 pandemic. In Study 1, conducted in April 2020, the participants were 402 male student-athlete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 39 publications
5
40
0
1
Order By: Relevance
“…These restrictions not only contributed to a heightened pressure to uphold expectations but also limited student athletes’ ability to de-stress. These findings build off recent quantitative work demonstrating significant correlations between student athlete social support, athlete identity, and mental health during the COVID-19 pandemic [ 17 , 18 ]. Together, these findings underscore the need to balance concerns over student athlete health and availability with their basic social needs.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These restrictions not only contributed to a heightened pressure to uphold expectations but also limited student athletes’ ability to de-stress. These findings build off recent quantitative work demonstrating significant correlations between student athlete social support, athlete identity, and mental health during the COVID-19 pandemic [ 17 , 18 ]. Together, these findings underscore the need to balance concerns over student athlete health and availability with their basic social needs.…”
Section: Discussionsupporting
confidence: 81%
“…The importance of social support to athlete identity and mental health [ 17 , 18 ] as well as return to sport following orthopedic surgery [ 5 , 6 ] have been noted. In the present study, social support, particularly from teammates who were going through the same experiences, was a commonly cited adaptive coping strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teammates and coaches are another important source of support for injured athletes during recovery from injury, especially for injured college-student athletes who are living away from home. Social support from one’s teammates and coaches may be particularly important during the COVID-19 pandemic as injured athletes may not be able to see their family/friends in-person during the athletic season or due to the mental health challenges associated with the pandemic itself [ 40 , 41 ]. It is, therefore, crucial that one’s teammates and coaches provide high levels of social support to injured athletes throughout their recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Athletic performance can be improved by sleep education, CBT, and prolonged sleep duration interventions 20) . Hagiwara et al (2021) reported on the social identity and mental health in student athletes and found a negative correlation among Japanese student athlete identity, depression, and sports helplessness. Additionally, they found a negative correlation among social support from teammates, depression, and sports helplessness 21) .…”
Section: Discussionmentioning
confidence: 99%